Whole transcriptome sequencing and integrated network analysis elucidates the effects of 3, 8-Di-O-methylellagic acid 2-O-glucoside derived from Sanguisorba offcinalis L., a novel differentiation inducer on erythroleukemia cells. (April 2021) - Long, Wang; Liu, Sha; Li, Xiao-Xuan; Shen, Xin; Zeng, Jing; Luo, Jie-Si; Li, Ke-Ru; Wu, An-Guo; Yu, Lu; Qin, Da-Lian; Hu, Guang-Qiang; Yang, Jing; et al.
Abstract: Acute erythroid leukemia (AEL) is a rare and aggressive hematologic malignancy with no specific treatment. Sanguisorba officinalis L. ( S. officinalis ), a well-known traditional Chinese medicine, possesses potent anticancer activity. However, the active components of S. officinalis against AEL and the associated molecular mechanisms remain unknown. In this study, we predicted the anti-AML effect of S. officinalis based on network pharmacology. Through the identification of active components of S. officinalis, we found that 3, 8-Di-O-methylellagic acid 2-O-glucoside (DMAG) not only significantly inhibited the proliferation of erythroleukemic cell line HEL, but also induced their differentiation to megakaryocytes. Furthermore, we demonstrated that DMAG could prolong the survival of AEL mice model. Whole-transcriptome sequencing was performed to elucidate the underlying molecular mechanisms associated with anti-AEL effect of DMAG. The results showed that the total of 68 miRNAs, 595 lncRNAs, 4030 mRNAs and 35 circRNAs were significantly differentially expressed during DMAG induced proliferation inhibition and differentiation of HEL cells. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses revealed that the differentially expressed miRNAs, lncRNAs, mRNAs and circRNAs were mainly involved in metabolic, HIF-1, MAPK, Notch pathway and apoptosis. The co-expression networks showed that miR-23a-5p, miR-92a-1–5p, miR-146b and miR-760 regulatory networks were crucial for megakaryocyte differentiation induced by DMAG. In conclusion, our results suggest that DMAG, derived from S. officinalis might be a potent differentiation inducer of AEL cells and provide important information on the underlying mechanisms associated with its anti-AEL activity. Graphical Abstract: ga1